PEMBERDAYAAN MASYARAKAT PESISIR DESA PENGUDANG DALAM PENINGKATAN KUALITAS LINGKUNGAN - Sidabutar, Yuanita FD; Bintang, Malahayati Rusli; Raymond; Hanifah; Putri , Nurul Hilda Syani; Fera , Mirta; Kareem, Zidan Dwi Khalfani; Risnawati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This community service activity was carried out in Pengudang Village, Bintan Regency, Riau Islands Province, which is a coastal area with abundant marine ecosystem potential but is experiencing environmental pressure due to community activities and minimal ecological awareness. The purpose of this activity is to increase community awareness, knowledge, and skills in maintaining and managing the coastal environment sustainably. The implementation methods used include counseling, recycling-based waste management training, mangrove planting activities, the formation of environmentally conscious communities, and discussion forums in designing local conservation-based policies. The activity was carried out on May 27, 2025 and involved various elements of society such as fishermen, housewives, students, and village officials. The results of the activity showed an increase in community understanding of the importance of environmental conservation.